A rare case of intrapulmonary teratoma - Bansod, Atish N.; Awachar, Neha S.; Umalkar, Rohan K.; Jatli, Manjunath C.; Tayade, Priyanka C.; Patil, Ishwar G. (International Surgery Journal, 2022)
Benign cystic teratomas of the lung are extremely rare. We diagnosed such case in 22 years old male suffering from heaviness in left side of chest for 2 years with occasional cough with expectoration for 1 year. Patient suffered typical symptom of white hair in expectoration. Diagnosis was confirmed on computed tomography thorax and Fine needle aspiration cytology. Teratoma was located in anterior segment of left upper lobe and was treated with left upper lobectomy. Histopathology was done and was implicational mature teratoma.